2008
DOI: 10.1182/blood.v112.11.4547.4547
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Transfusion Practices: High Dose Aminocaproic Acid and Vitamin K for the Management of Thrombocytopenia

Abstract: Aminocaproic acid (Amicar), an inhibitor of fibrinolysis, is indicated for the management of bleeding in thrombocytopenia, hepatic cirrhosis, cardiac surgery and neoplastic disease, such as cancer of the prostate, lung, stomach and cervix (package insert). Vitamin K, administered concurrently with aminocaproic acid, aids in coagulation through stimulation of clotting factors II, VII, IX and X (Pereira and Phan 2004). Though aminocaproic acid has been available since 1964, there is limited use of the drug withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The cost of aminocaproic acid is approximately $5.00 dollars per tablet, making it a cheap option and cost-effective drug. 44 A previous study reported the oral TXA dosage cost of $14.00 dollars per tablet. 9 The potential cost-saving benefits of oral aminocaproic acid are especially great because total knee arthroplasty is a highvolume procedure, and the cumulative effect of per-patient savings becomes amplified on larger scales.…”
Section: Discussionmentioning
confidence: 99%
“…The cost of aminocaproic acid is approximately $5.00 dollars per tablet, making it a cheap option and cost-effective drug. 44 A previous study reported the oral TXA dosage cost of $14.00 dollars per tablet. 9 The potential cost-saving benefits of oral aminocaproic acid are especially great because total knee arthroplasty is a highvolume procedure, and the cumulative effect of per-patient savings becomes amplified on larger scales.…”
Section: Discussionmentioning
confidence: 99%